Seasonal Characteristics of Volatile Organic Compounds in Seoul, Korea: Major Sources and Contribution to Secondary Organic Aerosol Formation - Yeonjung Lee; Soo Ran Won; Hye Jung Shin; Dae Gon Kim; Ji Yi Lee (Aerosol and Air Quality Research)
Abstract Volatile organic compounds (VOCs) are major pollutants that cause air pollution and are precursors that react in the air to produce secondary organic aerosol (SOA). This study attempted to elucidate the distribution characteristics of VOCs in the atmosphere of Seoul by measuring 34 types of VOCs in real time in the winter of 2020 and summer of 2021. The objectives of this research are as follows: (1) understand the characteristics of VOCs in Seoul and the difference between winter and summer compositions, (2) identify the main sources of VOCs in winter and summer, and (3) estimate the contribution of VOCs to the SOA formation potential in Seoul. Total VOC concentrations were found to be higher in summer (7.61 ± 4.22 ppb) than in winter (6.28 ± 4.11 ppb). To further specify the cause of the difference in major VOC components in winter and summer, a cause analysis was performed using the ratio between marker components, and an emission source analysis of VOCs was performed by applying the positive matrix factorization model (PMF). The source distribution of VOCs in Seoul was attributed to five factors: solvent usage, vehicle exhaust, industry/burning of fossil fuels, petrochemical industry, and road emission (winter)/gasoline-related (summer). The contribution of VOCs to SOA formation was estimated using the secondary organic aerosol formation potential. The results showed that toluene was the primary contributor to SOA formation in both winter and summer. In the summer, solvent usage containing high proportion of ethylbenzene and xylenes contributed more than twice as much to SOA formation compared to the winter.